Lembar Kerja Siswa (LKS) Matematika Berbasis Guided Discovery Learning Siswa Kelas IX SMP - Muliarsih, Leni; AS, Rusdy; Heru, Heru (Universitas Muhammadiyah Palembang, 2021)
This study aims to produce teaching materials in the form of LKS based on Guided Discovery Learning for class IX students of SMP. The research method used is development research, consisting of a preliminary research phase, a prototype phase, and an assessment phase. The subjects in this study were class IX students of SMP Muhammadiyah 1 Palembang, totalling 32 students. The prototype in the form of worksheets in this study was validated by media, material and language experts. Based on the validation results of the experts, it was stated that the LKS prototype was valid. The second prototype (LKS) was tested for practicality through the small group test and obtained 93.33%, which was categorized as practical. A field test was carried out to see the potential effect of the developed LKS and obtained an average student final score of 80.96. The result shows that the worksheets developed and tested are categorized as very good. Based on the study results, it can be concluded that the student worksheets based on guided discovery learning that have been developed are valid, practical and have a potential effect on student learning outcomes